Design of Border Irrigation System Using SURDEV for Medium Soils - Aggarwal, Rajan; Kaur, Samanpreet; Garg, Sunil; Reeta, Kumari (Journal of Agricultural Engineering, 2007)
Border irrigation method is used to irrigate most of the field crops. Accurate design and high quality optimization of the border irrigation system is necessary for efficient and judicious use of water resources. SURDEV was used for the design and evaluation of border irrigation system for medium soils for irrigation depth 75 mm, stream size of 10, 15, 20, 30, 45 and 60 I/sec and border length of 60, 90, 120, 150 and 180 m. The outputs of SURDEV provided optimum field dimensions for irrigating the small-drilled grain crops in medium textured soils.